Therapeutic Potential of Secreted Amyloid Precursor Protein APPsα - Mockett, Bruce G.; Richter, Max; Abraham, Wickliffe C.; Müller, Ulrike C. (Frontiers in Molecular Neuroscience, 2017)
Cleavage of the amyloid precursor protein by α-secretase generates an extracellularly released fragment termed secreted amyloid precursor protein-alpha (APPsα). Not only is this process of interest due to the cleavage of APP within the amyloid-beta sequence, but APPsα itself has many physiological properties that suggest its great potential as a therapeutic target. For example, APPsα is neurotrophic, neuroprotective, neurogenic, a stimulator of protein synthesis and gene expression, and enhances long-term potentiation and memory. While most early studies have been conducted in vitro, effectiveness in animal models is now being confirmed. These studies have revealed that either upregulating α-secretase activity, acutely administering APPsα or chronic delivery of APPsα via a gene therapy approach can effectively treat mouse models of Alzheimer’s disease and other disorders such as traumatic head injury. Together these findings suggest the need for intensifying research efforts to harness the therapeutic potential of this multifunctional protein.